(untitled) (Research, Society and Development, 2023)
The elucidation of paucibacillar cases, oligosymptomatic form and nonspecificity of symptoms hinder the diagnosis of TB in children under 10 years of age. In this sense, this study aimed to analyze the association of tuberculosis characteristics among children and adolescents in Porto Velho-RO. Cross-sectional study with a quantitative approach carried out from the records of tuberculosis cases, with children under 18 years of age and residing in the city, in the Information System for Notifiable Diseases, in the period from 2008 to 2018. The data were analyzed using frequency distribution, Chi-square test and Fisher’s exact test, as well as residual analysis to verify the association, considering a significance level of 5%. It was found that, in the period analyzed, there was a statistical difference for education (p=0.001), sputum smear microscopy (p=0.009), chest X-ray (p=0.035), notification health unit (p=0.000) and treatment (p=0.000), in addition to the closure status (p=0.003). Although some variables did not present statistically significant differences between children and adolescents, it is important to reflect on the actions performed and fill in the information system for the formulation of actions and strategies. In view of these findings, it is necessary to implement strategies aimed at meeting the particularities of this public, identifying tuberculosis cases early and articulating the different levels of care for the management and co-management of tuberculosis cases, with protagonism and resolute insertion by the Care Primary to Health.